Pyronaridine–artesunate or dihydroartemisinin–piperaquine versus current first-line therapies for repeated treatment of uncomplicated malaria: a randomised, multicentre, open-label, longitudinal, controlled, phase 3b/4 trial. Issue 10128 (7th April 2018) - ,; Sagara, Issaka; Beavogui, Abdoul Habib; Zongo, Issaka; Soulama, Issiaka; Borghini-Fuhrer, Isabelle; Fofana, Bakary; Traore, Aliou; Diallo, Nouhoum; Diakite, Hamadoun; Togo, Amadou H; Koumare, Sekou; et al.
Summary: Background: Artemether–lumefantrine and artesunate–amodiaquine are used as first-line artemisinin-based combination therapies (ACTs) in west Africa. Pyronaridine–artesunate and dihydroartemisinin–piperaquine are potentially useful for diversification of ACTs in this region, but further safety and efficacy data are required on malaria retreatment. Methods: We did a randomised, multicentre, open-label, longitudinal, controlled phase 3b/4 clinical trial at seven tertiary centres in Burkina Faso, Guinea, and Mali. Eligible participants for first malaria episode and all retreatment episodes were adults and children aged 6 months and older with microscopically confirmed Plasmodium spp malaria (>0 to <200 000 parasites per μL of blood) and fever or history of fever in the previous 24 h. Individuals with severe or complicated malaria, an alanine aminotransferase concentration of more than twice the upper limit of normal, or a QTc greater than 450 ms were excluded. Using a randomisation list for each site, masked using sealed envelopes, participants were assigned to either pyronaridine–artesunate or dihydroartemisinin–piperaquine versus either artesunate–amodiaquine or artemether–lumefantrine. Block sizes were two or four if two treatments were allocated, and three or six if three treatments were allocated. Microscopists doing the parasitological assessments were masked to treatment allocation. All treatments were once-daily or twice-daily tablets or granules given orally and dosed by bodyweight over 3 days at the study centre. Patients were followed up as outpatients up to day 42, receiving clinical assessments on days 0, 1, 2, 3, 7, 14, 21, 28, 35, and 42. Two primary outcomes were compared for non-inferiority: the 2-year incidence rate of all microscopically confirmed, complicated and uncomplicated malaria episodes in patients in the intention-to-treat population (ITT; non-inferiority margin 20%); and adequate clinical and parasitological response (ACPR) in uncomplicated malaria across all episodes (unadjusted and PCR-adjusted for Plasmodium falciparum and unadjusted for other Plasmodium spp) in the per-protocol population on days 28 and 42 (non-inferiority margin 5%). Safety was assessed in all participants who received one dose of study drug. This study is registered at the Pan African Clinical Trials Registry (PACTR201105000286876). Findings: Between Oct 24, 2011, and Feb 1, 2016, we assigned 4710 eligible participants to the different treatment strategies: 1342 to pyronaridine–artesunate, 967 to artemether–lumefantrine, 1061 to artesunate–amodiaquine, and 1340 to dihydroartemisinin–piperaquine. The 2-year malaria incidence rate in the ITT population was non-inferior for pyronaridine–artesunate versus artemether–lumefantrine (1·77, 95% CI 1·63–1·93 vs 1·87, 1·72–2·03; rate ratio [RR] 1·05, 95% CI 0·94–1·17); and versus artesunate–amodiaquine (1·39, 95% CI 1·22–1·59 vs 1·35, 1·18–1·54; RR 0·97, 0·87–1·07). Similarly, this endpoint was non-inferior for dihydroartemisinin–piperaquine versus artemether–lumefantrine (1·16, 95% CI 1·01–1·34 vs 1·42 1·25–1·62; RR 1·22, 95% CI 1·06–1·41) and versus artesunate–amodiaquine (1·35, 1·21–1·51 vs 1·68, 1·51–1·88; RR 1·25, 1·02–1·50). For uncomplicated P falciparum malaria, PCR-adjusted ACPR was greater than 99·5% at day 28 and greater than 98·6% at day 42 for all ACTs; unadjusted ACPR was higher for pyronaridine–artesunate versus comparators at day 28 (96·9% vs 82·3% for artemether–lumefantrine and 95·6% vs 89·0% for artesunate–amodiaquine) and for dihydroartemisinin-piperaquine versus comparators (99·5% vs 81·6% for artemether–lumefantrine and 99·0% vs 89·0% for artesunate–amodiaquine). For non-falciparum species, unadjusted ACPR was greater than 98% for all study drugs at day 28 and at day 42 was greater than 83% except for artemether–lumefantrine against Plasmodium ovale (in ten [62·5%] of 16 patients) and against Plasmodium malariae (in nine [75·0%] of 12 patients). Nine deaths occurred during the study, none of which were related to the study treatment. Mostly mild transient elevations in transaminases occurred with pyronaridine–artesunate versus comparators, and mild QTcF prolongation with dihydroartemisinin-piperaquine versus comparators. Interpretation: Pyronaridine–artesunate and dihydroartemisinin–piperaquine treatment and retreatment of malaria were well tolerated with efficacy that was non-inferior to first-line ACTs. Greater access to these efficacious treatments in west Africa is justified. Funding: The European and Developing Countries Clinical Trial Partnership, Medicines for Malaria Venture (Geneva, Switzerland), the UK Medical Research Council, the Swedish International Development Cooperation Agency, German Ministry for Education and Research, University Claude Bernard (Lyon, France), University of Science, Techniques and Technologies of Bamako (Bamako, Mali), the Centre National de Recherche et de Formation sur le Paludisme (Burkina Faso), Institut de Recherche en Sciences de la Santé (Bobo-Dioulasso, Burkina Faso), and Centre National de Formation et de Recherche en Santé Rurale (Republic of Guinea).